Edukasi Kesehatan Pentingnya Dukungan Keluarga dan Masyarakat Serta Keberadaan PMO (Pengawas Minum Obat) Terhadap Pasien Tuberkulosis - Handayani, Rini; Muda, Cut Alia Keumala; Nurmawaty, Dwi; Ramadhania, Ramadhania; Tolego, James Arnold; Rahma, Fani Dwi; Damayanti, Hazfrina; Lutfiyah8, Evi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2025)
Tuberculosis (TB) patients need at least 6 months of uninterrupted medication to be cured of TB. During this time, patients may experience forgetfulness, laziness, and boredom. Therefore, it is necessary to have the support of the family, community and the participation of Drug Drinking Supervisors (PMOs) in the success of TB patients' drug-taking efforts. Based on preliminary studies, it is also known that patients feel less support from family and community and the role of PMOs is not working well. The purpose of this activity is to increase awareness and knowledge of health cadres regarding the importance of family and community support and the existence of PMOs for TB patients. This activity was carried out in the form of counseling and provision and practice of filling out the PMO pocket book. The participants of this activity were 22 health cadres in the working area of the Tamansari District Health Center. The results of this activity are an increase in the percentage of correct answers from participants related to the material presented (range of percentage increase 22.7%-44.4%), participants can understand and fill in the PMO pocket book correctly, and there is feedback related to the PMO pocket book which is well received by cadres by suggesting changes in the font of the writing in the book to be larger. So, community service activities in the form of counseling and introduction of PMO pocketbooks can increase awareness and knowledge of health cadres regarding the importance of family, community and PMO support.